Tawny Emperor butterfly Asterocampa clyton (Boisduval & LeConte) (Insecta: Lepidoptera: Nymphalidae: Apaturinae) - Donald W. Hall (EDIS)
The tawny emperor is a medium sized, non-descript butterfly that is common in riparian forests, but is also found in dry woods and suburbs. Larvae that develop in fall overwinter in small groups in a hibernaculum constructed by tying leaves together with silk so it stays on the tree throughout the winter. This 8-page fact sheet was written by Donald W. Hall and published by the UF Department of Entomology and Nematology, June 2012.